2009
DOI: 10.1159/000260087
|View full text |Cite
|
Sign up to set email alerts
|

Differential Mucosal IL-17 Expression in Two Gliadin-Induced Disorders: Gluten Sensitivity and the Autoimmune Enteropathy Celiac Disease

Abstract: Background: The immune-mediated enteropathy, celiac disease (CD), and gluten sensitivity (GS) are two distinct clinical conditions that are both triggered by the ingestion of wheat gliadin. CD, but not GS, is associated with and possibly mediated by an autoimmune process. Recent studies show that gliadin may induce the activation of IL-17-producing T cells and that IL-17 expression in the CD mucosa correlates with gluten intake. Methods: The small-intestinal mucosa of patients with CD and GS and dyspeptic cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
169
1
4

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(188 citation statements)
references
References 32 publications
14
169
1
4
Order By: Relevance
“…As other studies have not shown changes in intestinal permeability and absorption ( 20,23 ), it could be hypothesized that the anemia and weight loss may in part depend on the self-restricted diet commenced by the patients, which excluded many foods. Th e other clinical characteristics are very similar to those observed in the allergic patients.…”
Section: Non-celiac Wheat Sensitivitymentioning
confidence: 99%
“…As other studies have not shown changes in intestinal permeability and absorption ( 20,23 ), it could be hypothesized that the anemia and weight loss may in part depend on the self-restricted diet commenced by the patients, which excluded many foods. Th e other clinical characteristics are very similar to those observed in the allergic patients.…”
Section: Non-celiac Wheat Sensitivitymentioning
confidence: 99%
“…Two recent studies have attempted to categorize GS further. Th e fi rst study (incorporating 13 active CD patients, 11 gluten-sensitive patients, and 7 controls) suggested that the mucosal expression of interleukin-17, an adaptive immune marker, was signifi cantly increased in celiac patients but not in GS patients ( 42 ). Furthermore, it was observed that the HLA DQ2 or DQ8 prevalence in GS was similar to controls (36 % for GS and 29 % for controls).…”
Section: What Evidence Is There To Support the Concept Of Non-celiac Gs?mentioning
confidence: 99%
“…The first recent description of NCGS has been reported by Sapone et al [8], while the existence of this condition has been confirmed by Biesiekierski et al [9 • ] in 2011, who demonstrated for the first time that individuals with a history of gluten sensitive symptoms did indeed respond to a double-blind gluten challenge. Since then, several reports from different groups have been published.…”
mentioning
confidence: 92%